Koncepcja Celestyna Freineta w pracy nauczyciela edukacji wczesnoszkolnej - Jędrzejowska, Agnieszka (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
Subject of my considerations is connected with integral teaching. Many of the goals of education that put Celestin Freinet pedagogy is close to the main purpose of education, which is to promote the comprehensive development of children. The development of these skills is dependent conditions. Freinet shows how these conditions should look like.Freinet said, my lab is a child. Accurate knowledge of child development by the teacher is the foundation for new thinking about education and teaching. Freinet perfectly noticed the shortcomings and disadvantages of traditional school. So, he created the concept of a school where children take into account the psychophysical predisposition, put the goal of preparing for life outside of school, live in cooperation and communication with people and live with possibility of creative, individual development.I would like to show in this article the Freinet techniques may support the development of a child by a teacher of early childhood education.